2004
DOI: 10.1023/b:bioc.0000006509.31571.a0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anthropogenic disturbance on plant diversity and community structure of a sacred grove in Meghalaya, northeast India

Abstract: This study analyses the effects of anthropogenic disturbance on plant diversity and community attributes of a sacred grove (montane subtropical forest) at Swer in the East Khasi Hills district of Meghalaya in northeast India. The undisturbed, moderately disturbed and highly disturbed stands were identified within the sacred grove on the basis of canopy cover, light interception and tree (cbh $ 15 cm) density. The undisturbed forest stand had .40% canopy cover, .50% light interception and a density of 2103 tree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
105
2
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(141 citation statements)
references
References 15 publications
26
105
2
8
Order By: Relevance
“…Simpson's index observed for herb layer was within the range of 0.06 to 0.09. Shannon Index diversity (Hʹ) and concentration of dominance (CD) were found inversely proportional to each other which have also been suggested by Misra et al [51]. The values of present study for (CD) fall within the reported values of Whittaker and Niering [52] and Risser and Rice [53] for temperate vegetation (0.01-0.99) [54].…”
Section: Diversity Indicessupporting
confidence: 90%
See 2 more Smart Citations
“…Simpson's index observed for herb layer was within the range of 0.06 to 0.09. Shannon Index diversity (Hʹ) and concentration of dominance (CD) were found inversely proportional to each other which have also been suggested by Misra et al [51]. The values of present study for (CD) fall within the reported values of Whittaker and Niering [52] and Risser and Rice [53] for temperate vegetation (0.01-0.99) [54].…”
Section: Diversity Indicessupporting
confidence: 90%
“…The values are more or less similar to reported values of (0.55 to 0.83), (0.93 to 0.99) and (0.92 to 0.96) for trees, shrubs and herbs in four sacred groves of Manipur. The values of present study are little more than reported value (0.4) for a sacred grove in Meghalaya north-east India [51].…”
Section: Diversity Indicescontrasting
confidence: 58%
See 1 more Smart Citation
“…Sacred groves of NE India are a reservoir of medicinal plants (Laloo et al 2006, Mishra et al 2004. The indigenous tribes have protected the groves since time immemorial due to their various religious beliefs attached to them.…”
Section: Ethnomedicinal Plants Of Northern Indiamentioning
confidence: 99%
“…Plant communities are separated from each other based on indicator species in combination with a distinctive floristic composition. The latter is considered as one of the major distinguishing characters of a community (Dansereau, 1960) and therefore, any depletion of biodiversity is bound to alter the community attributes (Mishra et al, 2004).…”
Section: Introductionmentioning
confidence: 99%